Image Framing of Indonesia's Constitutional Court in Tempo.co News (18-27 October 2023) - Audillah, Faiq Zaen; Fajrini, Nurkhalila (Yayasan Ilomata, 2024)
The Constitutional Court of the Republic of Indonesia (MK) plays a crucial role in reviewing laws against the 1945 Constitution and resolving election disputes, ensuring adherence to constitutional principles. Tempo.co, a prominent media outlet, has extensively covered the MK, especially following the recent controversy over the Court's ruling on age limits for presidential and vice-presidential candidates. This research examines how Tempo.co frames its coverage of the MK using Robert N. Entman’s framing analysis model, alongside agenda-setting theory and media reality construction theory. Applying a qualitative methodology, the study analyzes Tempo.co’s news articles from October 18 to October 27, 2023. The analysis reveals that Tempo.co employs various framing techniques consistent with Entman's model, which influences public perception through agenda-setting by emphasizing specific aspects of the MK’s activities. Additionally, the coverage constructs a particular narrative about the MK's role and decisions. To ensure data validity, thorough checks were performed. Findings indicate that Tempo.co’s headlines generally maintain neutrality and do not exhibit overt political bias, focusing on the institution’s functions. This research offers insights into how media framing, through Entman's model, agenda-setting, and reality construction, shapes the portrayal of significant constitutional issues and affects public understanding of the MK.